Ultrasonic-assisted chitin nanoparticle and its application as saltiness enhancer - Prachern Somsak (2020)
© 2020 Institute of Food Science and Technology This study was performed to evaluate some physical properties and potential application as saltiness enhancer of ultrasonic-assisted chitin nanoparticle prepared from shrimp shell (CSh) and/or squid pen (CSq). α-chitin and β-chitin were isolated, respectively, from shrimp shell and squid pen, and subjected to ultrasonication to obtain chitin nanoparticle. The ultrasonication time was varied at 30, 45 and 60 min, resulting in different sizes (diameter, nm) of chitin nanoparticle as follows: 41.33, 35.00 and 32.67, respectively, for CSh, while 50.67, 43.83 and 42.60, respectively, for CSq. The zeta potentials of CSh and CSq corresponding to the ultrasonication time were −31.37, −33.47 and −33.82 mV, and −29.81, −29.99 and −30.67 mV, respectively. Based on FTIR, ultrasonication time had negligible effects on chitin nanoparticle chemical structure. Results from sensory descriptive analysis showed that as ultrasonication time increased, saltiness intensity of chitin nanoparticle increased. CSh/CSq nanoparticle can potentially serve as a saltiness enhancer.